Interdisciplinary Collaborative Study on Scopus Indexed Publications of Universitas Terbuka Academic Staff 1988-2022 - Mohamad Pandu Ristiyono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Lecturers whose duties are research are communities of creators and users of scientific knowledge who have an important role in the creation of knowledge through scientific research or studies, are required to have knowledge in order to achieve scientifically justifiable results. Collaboration is a combination of several bibliometric elements, measurement is the main benchmark. The purpose of the study was to determine the impact of publishing scientific papers at the Indonesian Universitas Terbuka indexed by Scopus using a collaborative approach. This research method consists of four stages, namely identification, data collection (Scopus metadata), pre-processing of data (Altmetrics extraction), and analysis of results. This research will analyze the impact of the publication of the Indonesian Universitas Terbuka Research which is indexed by Scopus from 1988 to 2022, totaling 329 documents with a collaborative approach and comparing them with bibliometric calculations. The results of this study show that the total collaboration data are 329 documents from 220 authors of the Universitas Terbuka. The total citations of scopus indexed Universitas Terbuka articles are 393 citations where the author of Fatia Fatimah's article entitled N-soft sets and their decision making algorithms has the most citations, namely 95 citations. Meanwhile, Andrianyansah is the most productive writer with 21 documents, of which 2 are the sole authors and the rest collaborate with other writers. Of the 20 subjects written by the staff of the Universitas Terbuka, the highest subject of Social sciences was 119 documents (22.9%).